The Isolation and Identification of H. pylori among Iraq patients with chronic gastric inflammation - saber, fatima omer; Ali, Maryam K. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: H. pylori is one of the gastrointestinal organisms in which more than half the world’s population was infected. The aim of this study was to Isolation, identity, and determine antibiotic susceptibility of H. pylori from samples of the patient (biopsies) using various procedures. Patients and methods: A total of 90(58 males, 32females) patients with different age groups from both genders are involved in this study suffering from dyspeptic symptoms They underwent diagnostic ‘upper’ gastrointestinal (G.I.) endoscopy at “Endoscopy unit of AL- Sadder Teaching Hospital in Baghdad “during the period November 2021 to March 2022. Results: The results showed a relationship between H. pylori infection occurrence and endoscopic ally diagnosed dyspeptic patients; it was recorded that H. pylori was isolated in 30 cases. Antibiotic resistance test for H. pylori isolates showing susceptibility to levofloxacin, clarithromycin, ciprofloxacin, and amoxicillin. Whereas all the tested isolates were appearing resistant to metronidazole, and tetracycline. Conclusion: The results showed a relationship between H. pylori infection occurrence and endoscopic ally diagnosed dyspeptic patients. Culture and antibiotic sensitivity assay for detection of H. pylori are more reliable in biopsies than urease tests. H. pylori isolates were sensitive to levofloxacin, clarithromycin, ciprofloxacin, and amoxicillin.